Differences in Ankle ROM Between Young Men and Women With a History of Ankle Sprain - Kim, Jung-Hyun; Sung, Eun-Sook (Sportverletzung · Sportschaden, 2019)
Background Ankle injuries are the most common injuries in sports. However, very little is known about sex differences in ankle range of motion (ROM) between ankle joints with an episode of ankle sprain (ASE) and those without an episode of ankle sprain (non-ASE). This study aimed to investigate the differences of ankle ROM between men and women with and without ASE.Methods 26 ASE had at least one episode of ankle injury in the last 6 to 12 months. 35 non-ASE served as a control group. All subjects were examined in supine position and the ankle ROM was calculated by the sum of inversion (IV), eversion (EV), plantar flexion (PF) and dorsiflexion (DF) in both ankles.Results Subjects with ASE had a significantly smaller ROM regarding EV than non-ASE subjects in both ankles. The male subjects with ASE had a significantly higher EV and IV compared with the female subjects. However, ROM in PF was significantly lower among men compared with women who had ASE.Conclusions Our findings suggest that the ROM after ASE affects PF in male and EV in female patients. This could point to sex-based prevention and rehabilitation after ankle injury.
Keywords: ankle; sex; range of motion; sprains